PENGARUH HEDONIC SHOPING MOTIVATION DAN STORE ATMOSPHERE TERHADAP IMPULSIVE BUYING PADA KONSUMEN MINISO KOTA BIMA - Nur Khusnul Hamidah; Hanifah Muthiah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
Seeing that business competition is currently getting tighter and more competitive. The needs and desires of society are increasingly complex, and consumers in the current era have various and increasing needs for products. making companies compete to innovate both in terms of place, service and products to be sold so that they can be accepted by consumers. Retail is an example of a commercial company that is growing rapidly in Indonesia. One of the few retail reconstructions is Miniso. This research aims to determine the influence of hedonic shopping motivation and store atmosphere on impulse buying. The research method used in this research is a quantitative research method with a sample size of 30 respondents. The data collection technique uses a questionnaire and the data analysis technique uses the classic assumption test and multiple linear regression test with hypothesis testing using the t test and F test.